Comparative efficacy and safety of Cilnidipine and Amlodipine in the management of hypertension - Hossain, Mohammed Akram; Ahsan, Md Farid; Biswas, Jadab Kumar; Farahnaj, Sara; Khan, Ashraful Alam (Ibrahim Cardiac Medical Journal, 2025)
Background & objective: Hypertensive patients with coronary artery disease and diabetes mellitus usually benefit from selective antihypertensive medications like calcium channel blockers (CCBs). Of the dihydropyridine (DHP) CCBs, amlodipine has an excellent pharmacokinetic and pharmacodynamic profile. The only drawback of amlodipine is that it causes pedal oedema leading to drug discontinuation in many cases. The new generation CCB, cilnidipine has demonstrated equal efficacy in controlling blood pressure, but its adverse effect as is observed in amlodipine has not been widely tested. The present study was, therefore, designed to make a comparative evaluation of cilnidipine and amlodipine in the management of blood pressure in hypertensive individuals. Patients & Methods: The present non-randomized clinical trial was conducted in the private practices of renowned cardiologists and specialists in internal medicine in Chittagong Metropolitan City over a period of four years, from January 2020 to December 2023. A total of 496 hypertensive patients of both sexes were consecutively enrolled in the study. Among them, 455 patients-246 in the Amlodipine group and 209 in the Clinidipine group completed the two scheduled follow-up visits within six months of the intervention (the study endpoint) and were subsequently included in the final analysis. The study drugs were considered effective if 80% of the subjects in the study experienced control of blood pressure (systolic blood pressure < 140 mmHg and/or diastolic blood pressure < 90 mmHg) after 6 months of intervention with the study drugs. The study drugs were termed safe if they did not cause impairment of renal, neuro, and cardiac functions significantly during the study period. Pedal oedema was assessed by clinical method over the medial malleolus of both legs. Result: The cilnidipine and amlodipine groups were comparable regarding age and sex. However, obesity and diabetes were more prevalent in the amlodipine group, while smokers were more frequent in the cilnidipine group. Mean systolic and diastolic blood pressures were slightly lower in the cilnidipine group. Fasting blood sugar levels were similar, and dyslipidemia was common in both groups. The comparative evaluation of cilnidipine and amlodipine in the management of systemic hypertension revealed significant differences in heir efficacy and safety profiles. Both medications effectively reduced blood pressure, with a greater mean reduction in systolic blood pressure being observed in the amlodipine group compared to the cilnidipine group (19.9% vs. 15.6%, p < 0.001). However, the incidence of adverse effects, particularly pedal edema, was notably higher in the amlodipine group (11% vs. 4.8%, p = 0.016), indicating a preference for cilnidipine among hypertensive patients concerned about tolerability. Despite these differences in side effects and blood pressure control, the overall efficacy in achieving target blood pressure levels (SBP < 140 mmHg and DBP < 90 mmHg) was comparable between the two groups, as evidenced by the high control rates of 87% in the amlodipine group and 88.5% in the cilnidipine group (p = 0.622). Conclusion: The study concluded that both cilnidipine and amlodipine are equally effective in reducing blood pressure in hypertensive individuals. However, cilnidipine is less likely to cause pedal oedema than amlodipine. This advantage of cilnidipine makes it a preferred antihypertensive drug over amlodipine. Ibrahim Card Med J 2024; 14(1): 19-27